2020
DOI: 10.1111/jphp.13285
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on pharmacokinetics and tissue distribution of 5-hydroxy-4-methoxycanthin-6-one and its metabolite in normal and dextran sodium sulfate-induced colitis rats by HPLC-MS/MS

Abstract: Objectives This study aimed to investigate the existing form of 5-hydroxy-4methoxycanthin-6-one (PQ-A) in vivo after oral administration and the effects on its pharmacokinetics and tissue distribution by colitis. Methods A rapid HPLC-MS/MS method was established to simultaneously determine PQ-A and its main metabolite, 1-methoxicabony-b-carboline (PQ-B), in biological samples acquired from normal and dextran sodium sulfate (DSS)induced colitic rats administered orally with PQ-A. Then, the pharmacokinetics of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Andrographolide (Lot number 110797-201609) and dehydroandrographolide (Lot number 110854-201710) were purchased from National Institutes for Food and Drug Control (Beijing, China). 1-methoxicabony-β-carboline and 4-methoxy-5-hydroxy-canthin-6-one were purified and identified using Infrared Spectroscopy (IR), UV–visible spectroscopy (UV), mass spectrometry (MS), and Nuclear Magnetic Resonance Spectroscopy (NMR) as described in our previous studies, and the purity of them was more than 98% ( Yang et al, 2016 ; Liu et al, 2020 ; Zhang et al, 2021 ). Chloramphenicol (Lot number Y27M6C2), internal standard (IS), was purchased from Shanghai Yuanye Bio-Technology Co., Ltd (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Andrographolide (Lot number 110797-201609) and dehydroandrographolide (Lot number 110854-201710) were purchased from National Institutes for Food and Drug Control (Beijing, China). 1-methoxicabony-β-carboline and 4-methoxy-5-hydroxy-canthin-6-one were purified and identified using Infrared Spectroscopy (IR), UV–visible spectroscopy (UV), mass spectrometry (MS), and Nuclear Magnetic Resonance Spectroscopy (NMR) as described in our previous studies, and the purity of them was more than 98% ( Yang et al, 2016 ; Liu et al, 2020 ; Zhang et al, 2021 ). Chloramphenicol (Lot number Y27M6C2), internal standard (IS), was purchased from Shanghai Yuanye Bio-Technology Co., Ltd (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…These days, ultra-high performance liquid chromatography coupled with electrospray ionization tandem quadrupole/time of flight mass spectrometry (UPLC-MS/MS) has been used as a general approach for metabolic and pharmacokinetic profiling study of natural products ( Yao et al, 2018 ; Li et al, 2019 ; Wu et al, 2020 ). Recent research has also shown that the internal environment could influence the pharmacokinetics of drugs in a pathological state, such as colitis ( Liu et al, 2020 ). It is indicated that pharmacokinetic study of XLF in UC state is necessary to provide a basis for clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Nigakinone (5-hydroxy-4-methoxycanthin-6-one) is the main effective component of Ramulus et Folium Picrasmae, a commonly used traditional Chinese medicine for the treatment of dysentery, colitis, and gastroenteritis (Liu et al, 2020). Pharmacological researches have proven that nigakinone possesses anti-inflammatory, anti-bacterial, and cyclic adenosine monophosphate (cAMP) phosphodiesterase inhibitory activities (Gong et al, 2018), and ameliorating effects on DSS-induced colitic rats.…”
Section: Introductionmentioning
confidence: 99%
“…In intoxication cases, the pharmacokinetics and excretion of these metabolites cannot be fully evaluated in many cases, because of the first sampling is performed during clinical cares after intoxication diagnosis. At this point, in vivo experiments in model animals provide information about the metabolism of a certain substance, as well as the distribution of the parent compound and/or metabolites in different tissues along the time, including the excretion of these compounds 25 .…”
Section: Introductionmentioning
confidence: 99%